Area of technical uncertainty for susceptibility testing of amoxicillin/clavulanate against Escherichia coli: analysis of automated system, Etest and disk diffusion methods compared to the broth microdilution reference. (December 2020) - Soares, A.; Pestel-Caron, M.; Leysour de Rohello, F.; Bourgoin, G.; Boyer, S.; Caron, F.
Abstract: Objectives: The European Committee on Antimicrobial Susceptibility Testing (EUCAST) recently warned about an area of technical uncertainty (ATU) of amoxicillin/clavulanate (AMX/C) disk susceptibility testing against members of the Enterobacterales. Thus, we aimed to compare the reliability of three routine methods and to evaluate the impact of the ATU. Methods: 286 Escherichia coli strains (including 159 AMX-resistant strains) were categorized for the two EUCAST AMX/C breakpoints by disk diffusion (Bio-Rad), the Phoenix automated system (Becton Dickinson) and the Etest (AES) compared to the broth microdilution reference method. Results: By microdilution, 84.2% of strains were AMX/C-susceptible using the urinary breakpoint (MIC ≤32 mg/L) and 62.2% using the systemic breakpoint (MIC ≤8 mg/L), with 63.6% of MICs between 4 and 16 mg/L. For the systemic breakpoint, category agreement (CA) and very major error (VME) were unacceptable for the Etest (71.7% and 27.3%), disk (73.1% and 23.4% at 19-mm cut-off) and to a lesser extent for the Phoenix system (83.6% and 10.5%). For disks, an unacceptable VME rate was observed for diameters up to 22 mm, probably due to overcharged disks. For the Etest, VMEs were high at 6 mg/L (46/63) and 8 mg/L (22/29). For the urinary breakpoint, CA was more acceptable for disk (88.9%) and Etest (84.3%) but was unevaluable for Phoenix. Conclusion: AMX/C susceptibility testing of E. coli for systemic breakpoint was unreliable with the three routine methods, explained mainly by the high prevalence ( 60%) of strains with microdilution MICs around the breakpoint (8 mg/L). Our data confirmed the EUCAST 19–20-mm ATU for disk and suggest introducing ATU for Etest MIC values of 6 and 8 mg/L.